Пух и перья: мысли и афоризмы / Козьма Прутков - Прутков Козьма (Антология мудрости, 2003)
Экземпляры: АБ (20151118) / Инвентарный номер: 60141 / Цена: 90.00 / Сис.шифр: 84(2Рос=Рус)5 / Авт.знак: П 85 / ГРНТИ: 17.82.90 / ББК: 84(2Рос=Рус)5-49